Network Pharmacology–Based Identification of Key Mechanisms of Xihuang Pill in the Treatment of Triple-Negative Breast Cancer Stem Cells - Zhang, Yu-Zhu; Yang, Jia-Yao; Wu, Rui-Xian; Fang, Chen; Lu, Hai; Li, Hua-Chao; Li, Dong-Mei; Zuo, Hua-Li; Ren, Li-Ping; Liu, Xiao-Yuan; Xu, Rui; Wen, Jia-Huai; et al. (Frontiers in Pharmacology, 2021)
ABSTRACT The Xihuang pill, which is an approved Chinese Medicine formula (state medical permit No. Z11020073), is a commonly used adjuvant drug for cancer patients in China. The Xihuang pill has a satisfactory effect in treating breast cancer in the clinic, especially triple-negative breast cancer (TNBC), which is the most aggressive type of breast cancer, and finite effective therapies. However, the mechanism of the Xihuang pill in treating TNBC remains unclear. The present study aims to explore the pharmacological mechanism of the Xihuang pill for treating advanced TNBC. We identified the main chemical components of the Xihuang pill by HPLC-Q-TOF-MS/MS. The 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) analysis shows that the Xihuang pill-containing serum had no obvious killing effect on any subtype of breast cancer cells, but it inhibited the mammosphere colony formation of two TNBC cell lines (4T1 and HCC1806 cells) and could enhance the inhibitory effect of paclitaxel (PTX) on the proliferation of 4T1 and HCC1806 cells when combined with PTX. Seventy-six active compounds in the Xihuang pill, their 300 protein targets, and 16667 TNBC stem cell-related genes were identified. The drug-herb-active compound-target gene-disease network, and enrichment analyses were constructed with 190 overlapping candidate targets. Through text mining and molecular docking, the target gene NR3C2 and active compound naringenin were selected for further validation. According to the TCGA database, we showed that a high expression of NR3C2 promoted a higher survival probability regarding overall survival (OS). The in vitro experiments indicated that naringenin presented identical effect to XS, possibly by regulating the NR3C2 expression. Overall, this study explored the effect of the Xihuang pill in treating advanced TNBC cells and showed that naringenin, which is the key active compound of the Xihuang pill, could lessen the stemness of TNBC cells to produce a synergistic effect on PTX by regulating the NR3C2 gene. Keywords: Xihuang Pill; TNBC; cancer stem cell; network pharmacology; naringenin; NR3C2